The burgeoning role of literature review articles in management research: an introduction and outlook - Sascha Kraus; Ricarda B. Bouncken; Alba Yela Aránega (Review of Managerial Science, 2024)
Abstract This article delves into the significance and utility of literature review articles in the field of management research, encompassing their three most prominent forms: structured literature reviews, bibliometric analyses, and meta-analyses. It discusses the evolving role of literature reviews as essential tools in a research process, their methodological intricacies, and their contribution to shaping the landscape of management studies. Through a thorough examination of their merits, limitations, and best practices, our article sheds light on how literature review articles serve as valuable resources for scholars, policymakers, and practitioners in the field of management. In addition, the article points towards opportunities for using AI tools, for example Google Colab, ChatGPT, Methods Wizards, or Petal for single or multiple stages and tasks of structured literature analyses.
Additional information: M1;M10;M19;M20
Keywords: 330; Structured; Systematic; Literature; Review; Management; Business; Bibliometrics; Artificial intelligence